2016
DOI: 10.11646/zootaxa.4097.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Laonice (Polychaete: Spionidae) from West and Southwest Africa

Abstract: Three new species of Laonice (Polychaete: Spionidae): L. galatheae, L. cricketae, L. olgae-are described from South and West Africa (along the coast from 31°14.1'S to 04°44'N) based on Danish and South African zoological collections. Arguments relative to the morphological heterogeneity of the genus Laonice are advanced. The arguments are based on the following characters: degree of fusion of prostomium with peristomium at the anterior margin, degree of variability of all numerical characters, arrangement of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These incomplete and fragmented individuals often lack crucial taxonomic characters, hampering their identification 5 . Nonetheless, the spionid genus Laonice Malmgren, 1867 6 is well studied, especially species from the deep sea of the North Atlantic 7–10 . To facilitate the identification of Laonice species extensive studies on species-specific characters were conducted and four subgenera were suggested based on morphological characters 8,11 .…”
Section: Introductionmentioning
confidence: 99%
“…These incomplete and fragmented individuals often lack crucial taxonomic characters, hampering their identification 5 . Nonetheless, the spionid genus Laonice Malmgren, 1867 6 is well studied, especially species from the deep sea of the North Atlantic 7–10 . To facilitate the identification of Laonice species extensive studies on species-specific characters were conducted and four subgenera were suggested based on morphological characters 8,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sikorski & Pavlova (2016) recognized four morphologically distinct groups within Laonice . We now believe these groups qualify for subgeneric status and formally name them here.…”
Section: Resultsmentioning
confidence: 99%
“…Nine or ten species belong to this subgenus: L. cirrata; L. brevicornis (Kinberg, 1866); L. bahusiensis Söderström, 1920; L. brevicristata; L. branchiata Nonato et al ., 1986; L. shamrockensis Sikorski, 2003; L. asaccata, L. antipoda Sikorski, 2011, L. cricketae Sikorski & Pavlova, 2016 and maybe L. pinnulata Radashevsky & Lana, 2009 (see Sikorski & Pavlova, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations